Possible Nouns for Visual Experiences: A Theory of the Vision-Language Interface - Francesco-Alessio Ursini; Paolo Acquaviva (Baltic International Yearbook of Cognition, Logic and Communication, 2019)
The relation between vision and language is analyzed through a formal statement of what defines objecthood in the two domains. An interpretation of independently-motivated approaches to vision and to the grammar of nominals allows us to define the connection between them as an “infomorphism” consisting of two functions. Visual and linguistic objects are only indirectly related: the functions range over types and tokens, whose map defines objecthood in each domain. We show how the inferences proved in this system are empirically correct, and we draw some conclusions about the import of our proposal on the role of language in cognition.